1988
DOI: 10.3109/00016348809004162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on Maternal Hemodynamics and Placental Blood Flow in Healthy Women

Abstract: Intervillous placental blood flow responses to standardized exercise during late pregnancy were studied using a Xenon technique in 25 healthy women. Thirteen of them were studied twice between the 32nd and 38th weeks of pregnancy, with mean 32 (range 22 to 40) days between the studies. At the end of a 6-min exercise, mean maternal heart rate had risen from 77 +/- 10 (SD) to 154 +/- 11 beats/min, amounting to 63% of maximal oxygen uptake. Stroke volume rose by 9%, cardiac output by 65% and cardiac index by 71% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Similar studies have concluded that, during normal pregnancy, a short submaximal exercise session has little effect on placental blood flow after exercise, (23,27,28) as it was found in this study, in which the uterine arteries showed no difference, and the umbilical artery revealed vasodilation with no clinical consequences, probably due to a fetal mechanism to ensure homeostasis. (24) …”
Section: Discussionsupporting
confidence: 86%
“…Similar studies have concluded that, during normal pregnancy, a short submaximal exercise session has little effect on placental blood flow after exercise, (23,27,28) as it was found in this study, in which the uterine arteries showed no difference, and the umbilical artery revealed vasodilation with no clinical consequences, probably due to a fetal mechanism to ensure homeostasis. (24) …”
Section: Discussionsupporting
confidence: 86%
“…Rauramo and Forss14 found unchanged uterine blood flow following exercise. However, the study used Xenon clearance techniques, and that methodology was probably not reflecting uterine artery volume flow.…”
Section: Discussionmentioning
confidence: 94%
“…One experimental study in pregnant sheep found reduced volume blood flow by 15–20% in response to different exercise regimens 13. Studies in pregnant women have produced contradictory results 1416. There are several Doppler ultrasound studies on exercise-related changes in umbilical and uterine artery waveforms,1720 but we have found no studies on uterine artery volume blood flow during strenuous exercise in pregnancy.…”
mentioning
confidence: 78%
“…Animal studies suggest decreased uterine blood flow during physical activity (5-8), but studies in women are inconclusive (9-11). Several studies have reported an increase in fetal heart rate during maternal physical activity (12-16), although changes in fetal heart rate may occur in response to maternal epinephrine and may not reflect a decrease in oxygen (12-15).…”
Section: Introductionmentioning
confidence: 99%